Beginning teachers' professional support: A mixed methods social network study. (July 2019) - Thomas, Laura; Tuytens, Melissa; Devos, Geert; Kelchtermans, Geert; Vanderlinde, Ruben
Abstract: Drawing theoretically from the social network perspective, this article focuses on the collegial support networks of two beginning teachers, and how this is related to their job attitudes. A whole-school survey to investigate the support network structure of their primary school team, and an in-depth interview with the beginning teacher to explore the content of the support they receive, were employed. The results revealed that having access to professional support for diverse challenges and from a number of colleagues is important for job attitudes. Implications for stimulating professional interactions among beginning teachers and their colleagues are provided. Highlights: The two beginning teachers differ in network structure and content. The beginning teacher with high job attitude scores has a more central position. The beginning teacher with high job attitude scores receives more diverse support. The insider and outsider perspective about access to support seem to match.